Peranan Motivasi Berwirausaha dan Lingkungan Keluarga Dalam Meningkatkan Sikap Kewirausahaan Mahasiswi - Fatharani, Afina; Mulyadi, Hari; Widjadjanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The present study seeks to investigate the effect of entrepreneurial motivation and family environment onentrepreneurial attitude of the students of UPI Bandung class of 2015. This study utilizes a verificative approach with survey explanatory method. The study involves 160 female bachelor degree students from class 2015 of UPI Bandung. The analysis technique used in this study is verificative techniques using multiple linear regression analysis. The findings in this study indicate that entrepreneurial motivation strongly influences entrepreneurial attitudes, the family environment is strong enough to influence entrepreneurial attitudes, and the stronger the entepreneurial motivation and a good family environment, the higher the entrepreneurial attitude